ANTIFUNGAL ACTIVITY OF NUTMEG MACE (Myristica Fragrans Houtt) ETHANOL EXTRACT AGAINST Candida spp. - Yandji, Muhammad Akbar; Astuty, Eka; Bandjar, Fitri Kadarsih (Folia Medica Indonesiana, 2025)
Candida infections are increasingly common worldwide and represent one of the leading causes of death after cardiovascular disease. There are three types of candida that often infect humans, namely Candida albicans, Candida tropicalis and Candida parapsilosis. In the standard treatment used, immunity and side effects of treatment have been found. Therefore, other treatment options are needed, one of which is by using mace (Myristica fragrans Houtt) which is a native plant of Maluku and has secondary metabolite compounds that can be antifungal agents. This study aims to test the ability of ethanol extract of mace nutmeg (Myristica fragrans Houtt) with concentrations of 5%, 10%, 25%, 50%, 75%, and 100% on the growth of Candida albicans ATCC 10231, Candida tropicalis ATCC 750, and Candida parapsilosis ATCC 22019. This study was conducted using the disc diffusion method (Kirby-Bauer). The results showed that the strongest inhibition zone was shown at a concentration of 100% against Candida tropicalis with an average inhibition zone diameter of 7.93 mm. Meanwhile, the lowest inhibition zone was shown at a concentration of 5% against Candida parapsilosis with an average inhibition zone of 3.25 mm. This research can be concluded that ethanol extract of mace nutmeg at all concentrations is able to inhibit the growth of Candida albicans, Candida tropicalis and Candida. parapsilosis.